Midterm Outcomes and Satisfaction After Hip Arthroscopy Are Associated With Postoperative Rehabilitation Factors. Issue 1 (22nd January 2021) - Amar, Eyal; Martin, RobRoy L.; Tudor, Adrian; Factor, Shai; Atzmon, Ran; Rath, Ehud
Background: Arthroscopic hip-preservation surgery is commonly performed to address nonarthritic sources of hip pain in young, active individuals. However, there is little evidence to support postoperative rehabilitation protocols, including the most appropriate frequency and length of individual formal physical therapy sessions. There is also a lack of information to look at patients' perceived value of their home program/self-practice in relation to outcomes. Purpose: To investigate postoperative rehabilitation factors after hip arthroscopy related to formal physical therapy and home program/self-practice and their correlation with patient outcomes and satisfaction. Study Design: Cohort study; Level of evidence, 3. Methods: A total of 125 patients who underwent hip arthroscopy for femoroacetabular impingement syndrome and a labral tear (75 men) were included. The mean age was 34.6 ± 14.4 years, and the mean follow-up time was 4.9 ± 1.6 years. Hip Outcome Score–Activities of Daily Living subscale (HOS-ADL) scores, overall satisfaction scores, and factors related to supervised physical therapy and home program/self-practice were collected. Correlations between continuous variables and differences in the length of individual formal physical therapy and patients' rating of the importance of their home program/self-practice between those who would and those who would not undergo surgery again were assessed. Results: The frequency and length of individual formal physical therapy sessions were significantly correlated with postoperative HOS-ADL scores ( r = 0.22, P = .014; and r = 0.24, P = .007, respectively) and level of satisfaction ( r = 0.24, P = .007; and r = 0.21, P = .02, respectively). The length of individual formal physical therapy sessions was significantly greater in those who noted they would undergo surgery again (35.3 vs 26.3; P = .033). A significant correlation was identified between the rating of the importance of their home program/self-practice and postoperative HOS-ADL scores ( r = 0.29; P = .001) and their level of satisfaction ( r = 0.23; P = .009). There was a significant difference in the rating of the importance of their home program/self-practice between those who would undergo surgery again and those who would not (8.9 vs 7.8; P = .007). Conclusion: Surgeons and physical therapists should emphasize the value of home program/self-practice when it comes to outcomes and may want to encourage their patients to participate in more frequent, longer, formal physical therapy sessions.